2021
DOI: 10.3390/su13158197
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Corporate Social Responsibility Disclosure and Its Impact on Financial Performance: The Case of Vietnam

Abstract: The study examines the impact of company size, industry sensitivity, government ownership, liquidity and company age on Corporate Social Responsibility Disclosure (CSRD) in 2019 annual reports of listed companies on the Vietnam stock market. We also consider the relationship between CSRD and the financial performance measured by return on assets (ROA) and return on equity (ROE). This study uses descriptive statistics and regression methods to test research hypotheses. The empirical findings show that company c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 66 publications
4
15
0
Order By: Relevance
“…The content analysis method is one of the most common and popular strategies for examining sustainability or environmental information documented in the annual report [93,94]. Many prior research relied heavily on corporations' annual reports as the primary source of sustainability or environmental data for SEA research [95][96][97]. As such, this study employs a content analysis method to extract carbon-specific data from the sampled corporations' annual reports.…”
Section: Research Instrument and Data Analysismentioning
confidence: 99%
“…The content analysis method is one of the most common and popular strategies for examining sustainability or environmental information documented in the annual report [93,94]. Many prior research relied heavily on corporations' annual reports as the primary source of sustainability or environmental data for SEA research [95][96][97]. As such, this study employs a content analysis method to extract carbon-specific data from the sampled corporations' annual reports.…”
Section: Research Instrument and Data Analysismentioning
confidence: 99%
“…At the same time, sufficient support for issuing global CSR certificates is not provided [11]. In cases where businesses communicate CSR activities, they are likely to announce them in their yearly report or, rarely, in a CSR report or sustainable report; however, the report indicators and methods are inconsistent [12]. Most companies take on CSR superficially and spontaneously due to their altruistic motives and do not put much effort into fulfilling their social responsibility.…”
Section: Introduction 1research Backgroundmentioning
confidence: 99%
“…In line with legitimacy theory, companies used CSR to respond to political and public pressure (Dowling & Pfeffer 1975;Moratis & Egmond 2018;Nguyen et al 2021). Despite Ismaeel et al (2021) reported an insignificant relationship between environmentally sensitive industries and CSR, Solikhah (2016) and Hrasky (2011) added that companies in the sensitive industry changed and improved their sustainability disclosures following to greater stakeholder awareness and pressure.…”
Section: Industry and Csrmentioning
confidence: 99%
“…On the contrary, opponents have argued that CSR in the sensitive industry sector cannot be fully trusted (Solikhah 2016). Companies involved in controversial sectors might have more robust initiatives to commit to CSR as a way of management's self-serving behaviour disguising their harmful business nature and accomplishing legitimacy (Nguyen et al 2021). Scholars have reported that companies in the sensitive industry disclose more CSR despite the arguments above.…”
Section: Industry Effects and Csrmentioning
confidence: 99%